PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MENINGKATKAN AKTIVITAS DAN KOMPETENSI BELAJAR BIOLOGI SISWA KELAS VII A SMP NEGERI 4 KERINCI - Susanti, Wahyu Indah; Rusdinal, Rusdinal; Sumarmin, Ramadhan (Kolaboratif, 2014)
Students’ activity and competency in learning Biology at VII A class of SMPN 4 Kerinci are not optimum yet. The variety of methods and strategies that were used did not increase students’ activity and competency yet. Thus, it is necessary to increase students’ activity and competency by implementing cooperative learning model of Think Pair Share type. The purpose af this research is to increase students’ activity and competency in learning Biology. This research was done at the second semester of VII A class SMPN 4 Kerinci in academic year 2013/2014. This research was done in two cycles. Each cycle consisted of three meetings. There are four phases in the cycle; planning, action, observation, reflection. The data were collected based on observation sheet and the results of final test. In this case, the observation sheet was fulfilled by observer and final test was given at the and of cycle. Observation sheet was used to know students’ activity and competency in learning process. The data based on students’ activity were analyzed by using the number of student percentage in each meeting. In the data analysis, it was found that in the both of the first and the second cycle. The students’ activity and competency were increase. Students’ activity was increase from 11,46%, 46,79% to 76,52%. The students’ achievement in pra cycle, the first and the second cycle were also increase. The students’ achievement involved the cognitive result, that is the number of students who passed were 45,83%, 62,50% to 87,50%, the students afective result were 29,69%, 49,99% to 75,34% and the students’ psychomotoric result were 34,36%, 51,64% to 67,93%. In general, it can be concluded that the use of cooperative learning model of Think Pair Share type can increase students’ activity and competency in learning Biology at VII A class of SMPN 4 Kerinci.